A case study on fair compensation to hand embroidery workers in India. (10th April 2020) - Bishnoi, Sushil Kumar; Kapoor, Shikha
Abstract : Purpose: The study aims to focus on developing a methodology of technical calculation for fixation of piece rate for embroidery homeworkers of fashion industry to ensure an ethical livelihood standard. The standardised methodology for wage fixation will ensure better payments for homeworkers with clarity down the supply chain and sustainability of pay scales that will in turn improve the homeworkers' impecunious living standards. The brands giving living wage will be benefitted in terms of savings on training costs, more stable work force, reliable services and enhancements to the reputation. Design/methodology/approach: Interviews of subcontractors and agents down the supply chain in a target region were conducted to know current practice of wage fixation. The influential parameters were work content, basic living expenses and necessary benefits under government policies. Based on the aforementioned parameters, a formula has been generated. The present study is an attempt to develop a standard methodology to be used for piece rate calculation to ensure fair compensation for homeworkers. Impact of increased earnings of home workers on garment free on board cost has also been analysed. Findings: As there is no uniformity in methodology used for piece rate calculation, and work content is not considered in calculating piece rate, the wage earned per month by homeworkers, minimum wage and living wage are INR 2, 860, 6, 998 and 8, 007, respectively. Homeworkers receive 54-58 per cent of total embroidery labour cost incurred by suppliers. It can be increased up to 75 per cent, which would result in increasing the wage earned per month by homeworkers to INR 4, 000. Originality/value: The impact of implementing the outcome of the study will increase the earnings of embroidery homeworkers and reduce wage inequality in women's favour, as there are more women than men in embroidery homeworking.